The asymmetric synthesis of (2S,3R)-capreomycidine and the total synthesis of capreomycin IB - DeMong, Duane Eugene, author; Williams, Robert M., advisor (Colorado State University. Libraries, 2003)
An efficient and asymmetric synthesis of the non-proteinogenic amino acid (2S,3R)-capreomycidine is presented. The synthesis features a novel aluminum enolate-aldimine reaction with a chiral glycinate, which sets both stereocenters. A concise and high-yielding approach to the unnatural amino acid (2S,3S)-β-hydroxyornithine is also reported. The key step in this approach is a boron-mediated aldol reaction with a chiral glycinate. Additionally, the first asymmetric syntheses of α-formylglycine dimethyl and diethyl acetals are described. This two-step approach employs a novel titanium enolate of a chiral glycinate, followed by addition of the requisite trialkyl orthoformate to provide a single diastereomer of the glycinate adduct. Hydrogenolysis provides the optically pure acetal of α-formylglycine. Finally, the total synthesis of capreomyc in IB is described. The synthesis features the incorporation of the previously prepared (2S,3R)-capreomycidine. Additionally, the number of protecting group manipulations required in the synthesis has been greatly reduced by the utilization of asparagine in the peptide preparations as a masked precursor to diaminopropanoic acid. Conversion of the asparagine residue to the diaminopropanoic residue is accomplished by a Hofmann rearrangement.
Keywords: Amino acids -- Synthesis